Common Pool Problems in Voluntary Municipal Mergers - Tuukka Saarimaa; Janne Tukiainen (European Regional Science Association (ERSA), 2014)
We analyse free-riding behaviour of Finnish municipalities prior to voluntary municipal mergers. The merger process creates a temporary common pool problem, because of a delay from the initial decision to the actual merger during which municipalities stay autonomous. Using a difference-indifferences strategy, we find that the stronger free-riding incentive a municipality faced the more it increased its debt and spent its cash reserves. These funds were spent mostly on investments and current expenditures. The results can be attributed to the "law of 1/n" rather than to responding to an anticipated loss of political power or voluntary transfers between merging municipalities. Besides providing a test of the law of 1/n, our results suggest that local jurisdiction mergers are likely to involve a substantial (one-time) cost due to free-riding. This leads to two policy implications. First, during a merger process, some financial constraints on the local level may be a good idea to mitigate common pool problems. Second, for the merger policy to achieve the goal of decreasing public spending without reducing service quality, the scale economies need to be fairly large. Our results should be of wider interest, not only because mergers are used extensively in various countries, but also because common pool problems are present in many other contexts, such as (local) governments bail outs.
Keywords: 330; Common pool; difference-in-differences; free-riding; law of 1/n; municipality mergers